IJTIHAD POLITIK NU: NEGARA PANCASILA ADALAH NEGARA ISLAM - Syarif, Fajar (Alfuad: Jurnal Sosial Keagamaan, 2019)
The debate over the relationship between religion and the state reappeared when the New Order regime was at its peak of power, the 1980s. This has a fundamental need to strengthen the Unitary State of the Republic of Indonesia (NKRI) and establish Pancasila as the only state ideology and the only principle for religious and social organizations. This need certainly created an extraordinary paradigmatic controversy among all components of the nation, especially Muslims: between following the political will of the New Order or remaining a supporter of the establishment of an "Islamic state", not a Pancasila state. This is a big dilemma for the Indonesian people which in reality consists of thousands of islands, hundreds of ethnicities and languages, and dozens of religions, while the majority of the population is Muslim where the idea of establishing an 'Islamic state' has not vanished from the ideals of a number of Islamic organizations or groups.